2012
DOI: 10.1186/1471-2458-12-s1-s10
|View full text |Cite
|
Sign up to set email alerts
|

Policy initiation and political levers in health policy: lessons from Ghana’s health insurance

Abstract: BackgroundUnderstanding the health policy formulation process over the years has focused on the content of policy to the neglect of context. This had led to several policy initiatives having a still birth or ineffective policy choices with sub-optimal outcomes when implemented. Sometimes, the difficulty has been finding congruence between different values and interests of the various stakeholders. How can policy initiators leverage the various subtle mechanisms that various players draw on to leverage their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 13 publications
3
31
0
Order By: Relevance
“…Policymakers in our study noted poor application of economic evaluation to evaluate earlier SWAp processes. This view corroborates exiting studies in Ghana that indicated misinformation and poor stakeholder understanding greeted some sector polices on sexual and reproductive health (Mayhew & Adjei, 2004;Seddoh & Akor, 2012). Evidence from policymakers in our study also points to the poor application of economic evaluations to inform reproductive priority setting and decision making over the years.…”
Section: Policy Setting and Decision Making Processessupporting
confidence: 74%
See 1 more Smart Citation
“…Policymakers in our study noted poor application of economic evaluation to evaluate earlier SWAp processes. This view corroborates exiting studies in Ghana that indicated misinformation and poor stakeholder understanding greeted some sector polices on sexual and reproductive health (Mayhew & Adjei, 2004;Seddoh & Akor, 2012). Evidence from policymakers in our study also points to the poor application of economic evaluations to inform reproductive priority setting and decision making over the years.…”
Section: Policy Setting and Decision Making Processessupporting
confidence: 74%
“…In Ghana, priority-setting for reproductive health service interventions is known to be rudimentary with little wider stakeholder involvement (Mayhew & Adjei, 2004;Seddoh & Akor, 2012). Recent evidence in Ghana shows progress on family planning access, knowledge and awareness for reproductive health care (GSS et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The papers by Agyepong and Adjei (2008) and Seddoh and Akor (2012) note this complexity. Actors and stakeholders who want to influence agendas need to pay attention to context and policy actors in any strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Explaining decision making processes within these domains can provide some guidance to health practitioners and analyst who wish to understand national level decision making processes and entry points into the pluralistic (Ministry of Health, 2007) and sometimes elitist Adjei, 2008, Seddoh andAkor, 2012) Ghanaian health sector. People who want to influence national level decisions can actively participate in one or more of these decision domains.…”
Section: Decision Making Processes Related To Maternal Health Policy mentioning
confidence: 99%
See 1 more Smart Citation